EFFICIENT METHODS IN BREEDING DAIRY CATTLE OF THE REPUBLIC OF KAZAKHSTAN - S. K. Abugaliyev; Yu. A. Yuldashbayev; A. D. Baimukanov; L. R. Bupebayeva (Scientific Journal of Pedagogy and Economics, 2019)
10077 heads of cows, daughters of 117 bulls belonging to 38 lines of 4 dairy breeds: Alatau, Holstein Black-and-white, Black-and-white,and Red Steppe were monitored. In terms of breeds, mothers of daughters of the selected Alatau bulls have had average productivity of 5515±170 kg, the Holstein black-and-white - 7871±182 kg, Black-and-white - 5741±149 kg, and the Red Steppe - 3917±104 kg. It was established that the average productivity of dairy cows in the republic of all types of farms was 5039±31 kg. The highest productivity of Holstein cows is 5280±67 kg, the smallest - of Red Steppe breed cows - 3518±38 kg. The difference between the productivity of Holstein and Alatau was 436 kg, with Black-and-white - 344 kg, with the Red Steppe - 1762 kg (P>0.999). In terms of fat and protein, cows of the Red Steppe breed have the highest rates (3.96±0.02% and 3.30±0.03%, respectively). In terms of fat content, cows of the Red Steppe breed prevail over the Alatau breed by 0.22% (P>0.999), over the Holstein - by 0.23% (P>0.999), over the Black-and-white - by 0.31% (P>0.999), the excess in protein content was: over Alatau by 0.11% (P>0.99), over Holstein - by 0.12% (P>0.99), over Black-and-white - by 0.25% (P>0.999). In the age aspect, it was established that dairy productivity is characterized by growth (4844...5679...5458 kg) by the second or third lactation and a gradual decrease (4716...4017 kg) by the fifth lactation, i.e. this breed is characterized by a constant milk yield level. On average, for all lactations, cows of this breed gave 5123±275.4 kg of milk. The nature of the dairy productivity flow of cows of the Black-and-white breed has a peculiar specificity. So, starting from the first lactation, when there was a maximum milk yield (4936±231 kg), then there was a gradual decrease by the fifth lactation, where the lowest productivity was noted. Nevertheless, the average milk yield for all lactations was 4671±190 kg, i.e. the potential of this breed is seen, as evidenced by the variability of this selection trait (32.0...50.7%). The productivity of Red Steppe breed cows of different genotypes averaged - 3904 kg of milk, fat content - 3.77%, and live weight - 487 kg. The yield of crossbred cows is higher than those of purebred Red Steppe by - 280-365 kg. The coefficient of full value of lactation in the Red Steppe of different genotypes is within 63.77- 69.83%, in the Black-and-white - 69.17%, the index of the full value of lactation is within 83.7-93.6% and 94.97%.